Research of the process of obtaining capillary-porous materials from metal powders for heat pipes - L. P. Pilinevich; M. V. Tumilovich; A. G. Kravtsov; D. M. Rumiantsav; K. V. Hryb (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2021)
Heat pipes are designed to effective removing heat from heating elements and reducing the temperature of various devices. Heat pipes with capillary porous structures are designed to operate under conditions of unfavorable gravity forces. Their main advantages are their high heat transfer capacity, as well as the ability to retain the coolant in a capillary-porous structure under dynamic power loads. The purpose of this work is to study the process of obtaining capillary-porous materials from metal powders for heat pipes with increased efficiency of using the vibration molding method. The article substantiates the relevance of creating heat pipes from metal powders. The information about the influence of the contact angle, surface tension and capillary pressure on the heat transfer capacity of a heat pipe is provided. It is shown that for the efficient operation of the heat pipe it is necessary to create such a capillary structure of the porous material, which could simultaneously provide a high speed of movement of the coolant and its rise to a given height. The above requirements can be satisfied by creating a capillary structure using powder metallurgy methods by optimizing the distribution of pore sizes. In this case, the most promising method seems to be the method of molding when applying a vibration to a mold with a powder. It is possible to obtain the required pore distribution in this way by choosing the correct particle size, shape and vibration parameters. This makes it possible to ensure the packing of particles in size, which affects their packing density, pore size, tortuosity and length of pore channels. The distribution of the maximum pore sizes over the thickness of the samples obtained from powders of various granulometric composition with the use of vibration has been investigated. As a result, a process was developed for obtaining capillary structures by the method of vibration molding of metal powders, depending on the size of the powder particles, the amplitude and frequency of vibration. It is shown that this method can provide a given pore distribution of the capillary structure for heat pipes, which makes it possible to increase their heat transfer capacity.